Assembly line synthesis of isoprene from formaldehyde and isobutene over SiO2-supported MoP catalysts with active deposited carbon. Issue 59 (28th July 2017) - Qi, Yanlong; Cui, Long; Dai, Quanquan; Li, Yunqi; Bai, Chenxi
Abstract : Isoprene was synthesized over MoP catalysts with active carbonaceous deposits in an "assembly line" process. Abstract : Isoprene is a very important monomer for synthetic rubber. Its synthesis in the presence of MoP catalysts via the vapour phase reaction of isobutene with formaldehyde has been studied. The catalysis by various catalysts was characterized by TG analysis, the low-temperature adsorption of nitrogen, XRD, element analysis, TPD, the FT-IR of adsorbed pyridine, XPS and MAS NMR. A chemical process was proposed and confirmed. Isoprene was synthesized in an "assembly line" process through different active sites at the surface of the MoP catalysts, where the active sites were derived from P and Mo species and deposited carbonaceous species. In the induction period, carbon species are preferentially deposited on P species, leading to a decrease in the active Mo and P species (active sites 1), accompanied with a burst in active carbonaceous species (active sites 2). This soundly describes the burst in catalyst capacity in the induction period, which then decreases over time on stream at the expense of the active carbonaceous species. Accordingly, through the prior formulation of sites 1 with sites 2 in a catalyst, the time-consuming induction period can be nearly eliminated. We also observed that a good ratio of these two active sites can efficiently retard the catalyst deactivation. This study clarifies the roles of acid sites and active species in MoP catalysts in the synthesis of isoprene and shows that their optimal ratio can help reduce the length of the induction period and extend the lifetime of the catalysts.